Industrial Park and Foreign Investment for Sustainable Development in Indonesia - Hasan Mustapa; Melda Ria Juwita; Yusuf Gumilar Sukma (Khazanah Sosial, 2021)
In this era of globalization, foreign investment no longer needs to be seen as a threat. On the other hand, foreign investment can be considered as a driving force for national development, including for Indonesia as a developing country, including the construction of Industrial Parks. This study aims to determine the potential and challenges of foreign investment in the development of industrial estates in Indonesia. This paper uses a qualitative descriptive method, where this study describes events that occur and is intended to describe existing phenomena, both natural and human engineering. As a result, this paper finds that the Indonesian government has begun to improve infrastructure so that it is also sufficient to be one of the supporting factors. With a good location and infrastructure, the company's business activities become more effective. And more importantly, the Indonesian government is also willing to provide some fiscal facilities and licensing facilities related to company activities even though they are slightly contrary to sustainable development. Therefore, this research will contribute to the process of increasing foreign investment for sustainable development in Indonesia.